Exploring the Active Conformation of Cyclohexane Carboxylate Positive Allosteric Modulators of the Type 4 Metabotropic Glutamate Receptor. Issue 12 (5th September 2014) - Rovira, Xavier; Harrak, Youssef; Trapero, Ana; González‐Bulnes, Patricia; Malhaire, Fanny; Pin, Jean‐Philippe; Goudet, Cyril; Giraldo, Jesús; Llebaria, Amadeu
Abstract The active conformation of a family of metabotropic glutamate receptor subtype 4 (mGlu4) positive allosteric modulators (PAMs) with the cyclohexane 1, 2‐dicarboxylic scaffold present in cis‐2‐(3, 5‐dichlorophenylcarbamoyl)cyclohexanecarboxylic acid (VU0155041) was investigated by testing structurally similar six‐membered ring compounds that have a locked conformation. The norbornane and cyclohexane molecules designed as mGlu4 conformational probes and the enantiomers of the trans diastereomer were computationally characterized and tested in mGlu4 pharmacological assays. The results support a VU0155041 active conformation, with the chair cyclohexane having the aromatic amide substituent in an axial position and the carboxylate in an equatorial position. Moreover, the receptor displays enantiomeric discrimination of the chiral PAMs. The constructed pharmacophore characterized a highly constrained mGlu4 allosteric binding site, thus providing a step forward in structure‐based drug design for mGlu4 PAMs.